Islamic Republic of Mauritania : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2015)
KEY ISSUES Context. Mauritania's economy has benefited from macroeconomic stability and high growth in the context of contained inflation, responsible macro-policies, high iron ore prices and scaled-up public investment. However, economic growth has not translated into broadly improved living standards and is being hit by a sharp decline in iron ore prices. Outlook and Risks. Although the outlook remains favorable, it hinges heavily on stabilizing iron ore prices and expanding mining capacity. Downside risks to the outlook dominate because iron ore prices may decline further in response to excess supply in the global market. Key Policy Recommendations. With high risk of debt distress and deteriorating terms of trade, Mauritania's fiscal policy needs to remain focused on consolidation to support fiscal sustainability. Over the medium term, a fiscal framework with a full-fledged fiscal rule will help prevent the boom-bust cycles that ensue from volatility in natural resource revenue, and with strengthened governance in managing mining wealth. The central bank should take advantage of the low-inflation environment to strengthen monetary policy formulation, gradually liberalize the foreign exchange market, and introduce liquidity support and banking resolution frameworks. The implementation of the recent FSAP recommendations should be pursued to enhance the stability of the financial sector stability. Economic diversification and inclusive growth are the foremost medium-term challenges. The authorities should accelerate structural reforms needed to raise Mauritania's potential growth, create jobs, and improve living standards for all Mauritanians. Article VIII. A comprehensive analysis of the foreign exchange market identified exchange restrictions and multiple currency practices (MCPs) subject to Fund approval under Article VIII. Effective November 20, 2013, the exchange rate regime is classified as 'stabilized' arrangement.